Avaliação de espaçamento convencional e linhas gêmeas sob densidade populacional para cultura do milho - Balem, Zenilson (2013)
The increase in maize productivity is directly linked to management practices, especially the manipulation of spatial arrangement of plants through changes in row spacing, plant density and distribution of plants in the row. These practices are important to maximize the solar radiation interception, optimize its use and enhance grain yield. In this context, this work aims at assessing different row spacings, conventional and twin-row in plant densities for maize (Zea mays L). The study was conducted in the Agronomy Course experimental area of the Federal Technological University of Paraná, Campus Pato Branco, in the agricultural year of 2011/2012. A randomized block design in a 2x5 factorial arrangement with four replications was used. The ten treatments consisted of combinations of two row spacings (twin line spacing (0.2 x 0.7 m) and conventional spacing (0.7 m)) and five plant population (50,000, 65,000, 80,000, 95,000 and 110,000 plants ha-1). During the development of the culture were evaluated female flowering, the presence of broken and lodged plants, the incidence of stalk disease and the severity of leaf and ear diseases. Assessments regarding biometric variables were evaluated by measuring the plant height, the insertion of the first ear and the stalk diameter. Assessments related to yield components were evaluated by the number of rows, number of kernels per ear, 1,000 grain mass, mass of ears and productivity. The grain mass was corrected to 13% moisture. Data were tabulated and submitted to the "F" test of analysis of variance. For row spacings, means were compared by Tukey test at 5% probability. The effect of plant population was subjected to analysis of variance and regression. The models were chosen based on the significance of the regression coefficients, using the "t" test at 5% probability and on the coefficient of determination. The plant and first ear heights had no significant change due the treatments. The row spacing significantly influenced the stalk diameter, number of rows, number of grains per ear, 1,000 grain mass, the mass of ears and the average productivity of maize, given that the best results were obtained when using the spacing twin-rows. Grain yield responded quadratically to increasing density, indicating that with 91,700 plants ha-1 would be achieved maximum technical efficiency for hybrid P30F36H in Pato Branco - PR. The hybrid P30F36H has adaptability to high plant densities and to the use of twin row spacing in the climatic conditions of this municipality.